RELATIONSHIP BETWEEN COPING STRESS STRATEGIES AND STRESS LEVELS IN POST DIVORCE WOMEN IN TUBAN RELIGIOUS COURTS - Safaah, Nurus; Saidah, Faridatus (Universitas Airlangga, 2020)
Introduction: Divorce is a complex problem for woman because it is an event that can cause psychological problems that have an impact on daily life causing stress. One way to deal with stress is to use the right coping stress strategy. The purpose of this study was to determine the relationship of coping stress strategies with stress levels in post-divorce women in the Tuban religious court. Methods : The study design uses correlation analytic with cross sectional time approach. The study population numbered 50 post-divorce women in the Tuban religious according to inclusion and exclusion criteria, the research sample used simple random sampling totaling 42 respondents. The independent variable is the stress coping strategy, while the dependent variable is the stress level. The instruments used ware the revised Way of Coping Questionnaire (WOCQ) and (Depression Anxiety Stress Scales) DASS 42 questionnaire. Results : The results of study were almost 14 (33.3%) post-divorce women using problem focused coping (PFC) coping strategies experienced mild levels of stress and a small percentage of 1 (2.4%) respondents used emotion focused coping (EFC) coping strategies severe stress level. Contingency coefficient test results obtained p = 0.004 if the value of α = 0.05, then p <α with moderate accuracy (c = 0.494). Conclusion : Based on the description, it can be concluded that there is a relationship between coping stress strategies and the level of stress in women after divorce in the Tuban religious court. Choosing the right coping stress strategy is very important to deal with stress levels in post-divorce women.